Prevalence of Anemia in Patients of Acute Coronary Syndrome: A Descriptive Cross-Sectional Study from Tertiary Care Centre of Eastern Nepal - Pandey, Naveen Kumar; Shrestha, Sanjay; Jaiswal, Lokesh Shekher (Journal of National Heart and Lung Society Nepal, 2026)
Background: Anemia in the setting of acute coronary syndrome (ACS) has been linked with increased severity of the disease and poor clinical outcomes, due to its reduced ability to carry oxygen, impaired vascular healing and inflammation, heightened risk of thrombosis and need for blood transfusions. This study aims to determine the prevalence of anemia in ACS and describe its association with clinical characteristics, severity and outcomes among patients of ACS presented to tertiary hospital of Nepal. Methods: This was a descriptive cross-sectional study where clinical and angiographic profile of patients presenting with ACS, between November 2023 and October 2024 were evaluated and analysed in relation to anemia. Statistical analysis was done using SPSS 23. Results: A total of 200 patients with ACS admitted in the study period were included in the study. Prevalence of anemia was 48.5%. It showed significant association with age (p=0.001). Among risk factors, only dyslipidaemia was significantly associated with anemia. Its association with severity of coronary artery disease in terms of vessels involved (p=0.002) and Gensini Score (p=0.006) were significant. Similarly, it was significantly associated with longer intensive care stay (p=0.005). Mortality was higher in anemic (12.37%) compared to non-anemic patients (4.85%), but the difference was not significant (p=0.127). Conclusion: Anemia is considerably prevalent in our population and is associated with higher severity of disease mortality. Identification of anemia can be an important tool in treatment and prognostication of the disease.